2018
DOI: 10.21037/jtd.2018.09.156
|View full text |Cite
|
Sign up to set email alerts
|

“For your eyes only”: ophthalmic complications following lung transplantation

Abstract: Ophthalmic complications in the lung transplant population are a little-known entity. It includes a spectrum of diseases ranging from infections such as cytomegalovirus (CMV) retinitis, herpetic keratitis, Pseudallescheria boydii to non-infectious complications such as posterior subcapsular cataracts (PSCs), cyclosporine retinopathy, and post-transplant lymphoproliferative disorder (PTLD). These diseases can be attributed to high levels of immunosuppression, advanced age, and drug-specific side effects. Underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Tarabishy et al found that the most common ocular abnormality following lung transplant was posterior subcapsular cataract, followed by infectious ocular complications 34 . High levels of immunosuppression, advanced age, drug-specific side effects, underlying comorbidities such as diabetes mellitus, have been suggested to play a role in pathogensis 35 . Although visual loss from CPB has been reported previously, to our knowledge there are no prior reports of ophthalmic artery level ischemia presenting with CRAO, AION, and bilateral ophthalmoloplegia in the English language ophthalmic literature.…”
Section: Discussionmentioning
confidence: 99%
“…Tarabishy et al found that the most common ocular abnormality following lung transplant was posterior subcapsular cataract, followed by infectious ocular complications 34 . High levels of immunosuppression, advanced age, drug-specific side effects, underlying comorbidities such as diabetes mellitus, have been suggested to play a role in pathogensis 35 . Although visual loss from CPB has been reported previously, to our knowledge there are no prior reports of ophthalmic artery level ischemia presenting with CRAO, AION, and bilateral ophthalmoloplegia in the English language ophthalmic literature.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 Other side effects of central line placement include pneumothorax, traumatic puncture of the thoracic vessels, and even traumatic puncture of intrathoracic organs. 4,5 However, ophthalmic complications are uncommon. While some ophthalmic complications are due to medication side effects, others are attributed to systemic immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…The infectious diseases include cytomegalovirus retinitis, herpetic keratitis, herpes zoster opthalmicus, rhino-orbital mucormycosis, and disseminated pseudallescheria boydii infection. 5 Noninfectious complications can be divided into non-neoplastic vs neoplastic. The non-neoplastic complications can be cyclosporine-induced retinopathy, posterior subcapsular cataract, and central retinal vein occlusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations